24 A non-randomized comparison of two paclitaxel-coated balloons for the treatment of coronary in-stent restenosis. (5th October 2017) - Colleran, R; Joner, M; Kufner, S; Altevogt, F; Neumann, F; Wahab, A; Richardt, G; Giacoppo, D; Cassese, S; Ibrahim, T; Laugwitz, K; Schunkert, H; et al.
Abstract : Aims: Treatment of coronary in-stent restenosis (ISR) with paclitaxel-coated balloons (PCB) is recommended in European guidelines (class I recommendation, level of evidence A). Although iopromide-based PCB have been studied in numerous randomised trials, there is a relative paucity of data regarding butyryl-tri-hexyl citrate (BTHC)-based PCB and there has been no prospective head-to-head comparison of these devices. The aim of this study was to compare iopromide- and BTHC-PCB with respect to angiographic and clinical outcomes. Methods: Patients with ISR lesions treated with iopromide- and BTHC-PCB enrolled in 2 consecutive multicentre randomised trials were included. Patients treated with iopromide-PCB were enrolled between August 2009 and October 2011; patients treated with BTHC-PCB were enrolled between June 2012 and December 2014. Inclusion criteria were ischemic symptoms or evidence of myocardial ischemia in the presence of a restenosis >50% located in a native vessel DES. Exclusion criteria included target lesion located in the left main stem or in a coronary bypass graft, acute ST-elevation myocardial infarction within the preceding 48 hours, cardiogenic shock, and severe renal insufficiency. The primary angiographic endpoint was binary angiographic restenosis at 6–8 months. The primary clinical endpoint was the composite of death, myocardial infarction or target-lesion revascularisation at 1 year. Multivariate analysis was performed to adjust for differences in baseline characteristics between treatment groups. Results: 264 patients were treated with iopromide-PCB (n=137) or BTHC-PCB (n=127). Baseline clinical characteristics were similar for both groups, apart from a higher incidence of hypertension and lower incidence of prior myocardial infarction in the iopromide-PCB group compared with the BTHC-PCB group. Treatment groups were well-matched in terms of baseline angiographic and procedural characteristics, apart from smaller vessel size (2.78 vs. 2.89 mm, p=0.02) and lower % diameter stenosis post-procedure (18.4 vs. 22.3%, p=0.001) in the iopromide-PCB group. Surveillance angiography at 6–8 months was completed in 84% of patients. The primary angiographic endpoint occurred in 39 (32.5%) vs. 32 (32.0%) patients in the iopromide-PCB vs. BTHC-PCB groups (Padjusted =0.99) (Figure 1). The primary clinical endpoint occurred in 32 (23.4%) and 29 (23.2%) patients in the iopromide-PCB and BTHC-PCB groups, respectively (Padjusted =0.96) (Figure 2). Rates of death (3 [2.2%] vs. 2 [1.6%], Padjusted =0.89), myocardial infarction (3 [2.2%] vs. 2 [1.6%], Padjusted =0.62), TLR (30 [22.0%] vs. 27 [21.7%], Padjusted =0.99) and target-lesion thrombosis (1 [0.7%] vs. 0 [0%], Padjusted =0.93) were similar in both groups. Conclusions: In patients treated for in-stent restenosis, iopromide-PCB and BTHC-PCB showed comparable angiographic and clinical outcomes at 1 year.